Pengembangan media pembelajaran game edukasi berbantuan genially terhadap kemampuan pemahaman konsep matematis siswa - Islami, Sukmawati Millenia; Juariah; Rachmawati, Tika Karlina (Papanda Publisher, 2025)
This research is motivated by the need to improve students' understanding of mathematical concepts, as well as the lack of appropriate mathematics learning media to facilitate this capability, particularly in the area of integers, which is not as straightforward as it seems. To address this issue, a mathematics educational game media assisted by Genially has been developed. This study aims to explore the development process, validity, practicality, effectiveness, and student responses to the educational game media assisted by Genially concerning integer material. The method used in this research is the Research and Development (R&D) ADDIE model (analysis, design, develop, implement, and evaluate). The participants in this study are 28 students from class VII-A at SMP PGII 1 Bandung. The instruments used include expert validation sheets, student practicality sheets, and effectiveness sheets in the form of a test on the understanding of mathematical concepts, as well as the student response survey. The results of this research and development indicate that the educational game media for mathematics assisted by Genially received the criteria of 'Valid' from both media and content experts, the practicality of the educational media received the criteria of 'Practical', the effectiveness of the educational media received the criteria of 'Effective', and the student responses received the criteria of 'Very Good'. Thus, the educational game media assisted by Genially is declared valid, practical, effective, and very good for use in improving students' understanding of mathematical concepts, contributing significantly to the enhancement of the quality of mathematics education, particularly in understanding mathematical concepts among students.